Virtual or Hybrid? Marketing Event in the Time of Covid-19 Pandemic - Noer, Mochammad Kresna; Ramadhanti, Tisyabella Rizki (Graduate School of Communication Universitas Bakrie, 2022)
This article compares the implementation of two different types and methods of marketing events or special events that were popular during the Covid-19 pandemic, namely virtual events and hybrid events. Using the case study method, we observed and interviewed key informants and conducted document searches related to a Job fair event and an automatic product launch. The study found that virtual events allow participants facing travel restrictions to stay connected and participate in an event. In contrast, hybrid events are the best option if the number of participants is a critical factor in the event's success. In addition, despite having shortcomings in sensory stimulation, virtual events excel in terms of cost efficiency and participant affordability. Therefore, for marketing events that aim to introduce high-involvement products, hybrid or direct events are more appropriate.